A possible role for metalloproteinases in renal cyst development - Obermüller, Nicholas; Morente Medina, Natividad; Kränzlin, Bettina; Gretz, Norbert; Witzgall, Ralph (American journal of physiology. Renal physiology, 2001)
The expansion of cysts in polycystic kidneys bears several similarities to the invasion of the extracellular matrix by benign tumors. We therefore hypothesized that cyst-lining epithelial cells produce extracellular matrix-degrading metalloproteinases and that the inhibition of these enzymes may represent a potential target for therapeutic intervention. Using in situ hybridization, we first analyzed the expression of membrane-type metalloproteinase 1 (MMP-14), an essential matrix metalloproteinase, of its inhibitor TIMP-2, and of the cytokine transforming growth factor (TGF)-β2 in the (cy/+) rat model of autosomal-dominant polycystic kidney disease. Upregulated MMP-14 mRNA was predominantly located in cyst-lining epithelia and distal tubules, whereas TIMP-2 mRNA was confined almost exclusively to fibroblasts. TGF-β2, a cytokine known to regulate the expression of matrix metalloproteinases and their inhibitors, was also expressed by cyst wall epithelia. We then treated (cy/+) rats with the metalloproteinase inhibitor batimastat for a period of 8 wk. The treatment with the metalloproteinase inhibitor batimastat resulted in a significant reduction of cyst number and kidney weight. Our study suggests that metalloproteinase inhibitors represent a new therapeutic tool against polycystic kidney disease, which should be applicable independently of the background of the disease.